Comparison of fluorotelomer alcohol emissions from wastewater treatment plants into atmospheric and aquatic environments - Chen C; Wang J; Li L; Xu WG; Liu JG*. (Environment Internatinal, 2020)
Recent studies have revealed that wastewater treatment plants (WWTPs) are an important source of fluorotelomer alcohols (FTOHs) in the environment. However, it remains unclear whether volatilization to the atmosphere or discharge with wastewater effluent into receiving water bodies is the dominant pathway through which FTOHs enter the environment; it also remains unclear how the relative importance of these two emission pathways varies among seasons and homologs. Here, we estimated the emissions of 6:2 and 8:2 FTOHs through these two pathways from a typical WWTP in Beijing, China, by measuring height-dependent air concentrations above the wastewater surface; we also measured wastewater concentrations among the four annual seasons. Our results showed that atmospheric emissions dominate total annual FTOH emissions, but are not dominant in every single season. Emission to the aquatic environment is dominant during seasons with less wind (i.e., summer and fall). While the abundance of 6:2 FTOH has increased in recent years, 8:2 FTOH remains the major FTOH homolog released into the environment in China. This study provides comprehensive information regarding FTOH emissions from WWTPs to the environment and practical guidance for future monitoring practices.